One-dimensional drainage of soil profile with root extraction - A. Zakaria, Abdul; Willardson, Lyman S. (Universiti Putra Malaysia, 1992)
A one-dimensiunal n1l1nrncalmodel was developed to solve an unsaturated flaw equation for a soil prafik that represents a soil-plant-water system with a shallow water table above an impermeable layer. The diffusivity form of the Richard's equation was solved using Crank Nicalson implicit finite difference scheme and a general Newton-Raphson interative method. The model was used to simulate volume tric moisture content, capillary pressure, and position of water tab. It was also used to simulate the cumulative soil water depltion" within" the soil profile. Result from the compare model compared re compared reasonably we" measured lysimeter data.